Pengaruh Zat Pengatur Tumbuh Alami dan Lama Perendaman terhadap Pertumbuhan Stek Buah Naga (Hylocereus costaricensis) - Novani, Anzeli Surya; Mulyani, Cut; Mardiyah, Ainul (Jurnal Ilmiah Pertanian ( JIPERTA), 2026)
This study aimed to determine the effect of natural growth regulators (ZPT) and soaking duration on the growth of dragon fruit cuttings (Hylocereus costaricensis). The experiment used a Randomized Block Design (RBD) with two factors: natural growth regulators (honey, shallot extract, and coconut water extract) and soaking durations (3, 5, 7, and 9 hours). Data were analyzed using ANOVA followed by an LSD test at a 5% significance level. The results showed that natural growth regulators significantly affected the percentage of live cuttings, shoot emergence time, number and length of shoots, and number and length of primary roots. The best performance was obtained from coconut water extract (Z3) with 9 hours of soaking (P4), producing the longest primary roots and the highest shoot number. The novelty of this study lies in testing the combination of coconut water extract and a longer soaking duration (9 hours), which has rarely been examined before, as an eco-friendly alternative to accelerate vegetative propagation in dragon fruit cultivation.